Human Service Organization (HSO) Study of the Indonesian Red Cross (PMI) in Health and Community Welfare Services in Bandung City - Yuliyantini, Yuliyantini; Suhara, Ero (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research is motivated by the importance of the HSO's task in improving social welfare efforts or providing social welfare services to individuals, groups, families and communities who experience social problems or as a "Human Service Organization". To bring about changes in attitudes and behavior and improve the community's ability to be able to solve the problems they face and carry out their social functions appropriately. Social organizations have various functions. As for the function of social organizations, especially in order to help the government or participate in carrying out management functions, this can be because social service organizations currently still tend to focus on charity and are not based on profit (non-profit oriented). This situation allows for quite a large influence in the service process to the community. Therefore, the existence and functioning of PMI will continue to be developed through good organizational management so that it can reach more people and be sustainable. Compiled from various research that has been carried out previously, the problems at PMI include the availability of a digital information system that can provide real-time data on blood needs and availability, human resources managing financial reports, reduced regeneration of PMI volunteers, team organization or governance. management, availability of blood stock and blood quality at certain moments, and limited donors who finance the PMI program (Dewi et al., 2022; Hernimawati et al., 2020; Khoiri et al., 2021; Lendryono, 2022; Rakhman et al., 2019) This research will describe how HSO management practices and collaboration practices exist at PMI Bandung City in Health and Community Welfare Services.This research is motivated by the importance of the HSO's task in improving social welfare efforts or providing social welfare services to individuals, groups, families and communities who experience social problems or as a "Human Service Organization". To bring about changes in attitudes and behavior and improve the community's ability to be able to solve the problems they face and carry out their social functions appropriately. Social organizations have various functions. As for the function of social organizations, especially in order to help the government or participate in carrying out management functions, this can be because social service organizations currently still tend to focus on charity and are not based on profit (non-profit oriented). This situation allows for quite a large influence in the service process to the community. Therefore, the existence and functioning of PMI will continue to be developed through good organizational management so that it can reach more people and be sustainable. Compiled from various research that has been carried out previously, the problems at PMI include the availability of a digital information system that can provide real-time data on blood needs and availability, human resources managing financial reports, reduced regeneration of PMI volunteers, team organization or governance. management, availability of blood stock and blood quality at certain moments, and limited donors who finance the PMI program (Dewi et al., 2022; Hernimawati et al., 2020; Khoiri et al., 2021; Lendryono, 2022; Rakhman et al., 2019) This research will describe how HSO management practices and collaboration practices exist at PMI Bandung City in Health and Community Welfare Services.